A Critical Appraisal of Aims-Based Curriculum from a Global South Perspective. (January 2022) - Siddiqui, Asim
Michael Reiss and John White, An Aims-Based Curriculum: The Significance of Human Flourishing for Schools . London: Institute of Education Press, 2013. 80 pp., 24.95 (paperback). ISBN: 139780854739981; 10085473998X